Feasibility Study to Connect All African Higher Education Institutions to High-Speed Internet : Cote d’Ivoire Case Study - World Bank (World Bank, Washington, DC, 2021)
The Government of Cote d’Ivoire considers information and communications technology (ICTs) as a key instrument for national development. Youth education and training are high priorities for Cote d’Ivoire. Through its national development plan Cote d’Ivoire aspires to become an ICT leader in the region. Access to quality higher education is considered a primary vehicle to equip the population with the necessary skills to promote the social and economic development of Cote d’Ivoire. As part of the digital economy for Africa (DE4A) initiative, the World Bank commissioned a feasibility study to develop an operational roadmap to connect all African higher education institutions (HEIs) to high-speed Internet. The initiative, in support of the African union digital transformation strategy for Africa (2020-2030), aims to digitally enable every African individual, business, and government by 2030. This report provides a detailed country-level assessment to connect all HEIs in Cote d’Ivoire to high-speed Internet as part of the feasibility study. Chapter one gives introduction. The report provides a country overview in chapter two to provide the national context. The connectivity gap has both a supply-side and a demand-side: chapter three explores the demand-side, focusing on ICT in the education sector and the challenges impacting the use of information and communication technologies for teaching, learning, and research - creating the pull factors; and chapter four examines the supply-side, the ICT sector’s key components and the challenges affecting high-speed connectivity. Chapter five presents a high-level summary of the Reseau Ivoirien de Telecommunication pour l’Enseignement et la Recherche (RITER), the Ivorian research and education network. Drawing on findings from the earlier chapters, chapter six discusses the cost of connecting all HEIs in Cote d’Ivoire to high-speed Internet. The conclusion is given in chapter seven, followed by the appendices.